Pengaruh Tata Kelola Perusahaan Dan Struktur Kepemilikan Terhadap Jumlah Pengungkapan PSAK Berbasis IFRS - Vanica Serly (Universitas Negeri Padang, 2017)
This study aims to determine the level of disclosure compliance with Indonesia Accounting Standard (PSAK) convergence to International Financial Reporting Standards (IFRS) in manufacture companies in 2011-2012. Furthermore, this study aims to determine the effect of the structure of corporate governance (CG), ownership structure and company characteristics to the level of disclosure compliance with Indonesia Accounting Standards convergence to IFRS. Structure of corporate governance is measured by proportion of independent commissioner and audit committee. While ownership structures are measured by ownership concentration, international ownership and institutional ownership. Company characteristics are measured by size of the company, profitability and leverage. These results indicate that the level of disclosure compliance with Indonesia Accounting Standards convergence to IFRS in the manufacture companies is 80.33%. The multiple regression test showed that structure of corporate governance variables that affect compliance is the proportion of independent commissioner, the number of audit committee, ownership concentration, international ownership, institutional ownership, profitability and leverage had no effect on the level of disclosure compliance with Indonesia Accounting Standards convergence to IFRS. While the variable, namely size of the company had effect on the level of disclosure compliance. The regression also showed that the variable had R2 = 0.109. it means that the independent variable only influence the dependent variable for 10.9%.